Factors influencing home modification of stroke patients - Wutichai Permsirivanich (2018)
Background: Home modification for stroke victims is often necessary to prevent falls and enable them to have a better quality of life. Up-to-date relationship between personal factors and home modifications in post-stroke patients has not been investigated. Objective: To identify significant personal factors influencing the requirement for home modification in post-stroke patients. Study design: Prospective, analytical study. Material and Method: Two hundred eighty one post-stroke patients were recruited from nine tertiary rehabilitation centers in Thailand. All patients received inpatient rehabilitation programs until either they reached the rehabilitation goals or registered two consecutive stable weeks as measured by their Barthel index score. Personal factors related to home modification were assessed at study entry, during hospital stay and at discharge. The correlation between personal factors and necessities of home modification in post-stroke patients were reported through univariate and multivariate modeling. Results: The results of univariate analysis showed that a low Barthel index score (≤ 14/20) (at baseline and discharge), low Brunnstrom stage of arm or leg (≤ IV / VI) at baseline, and intolerance to intensive rehabilitation programs (< 3 hr / day) indicated a necessity for modifications in the patient's home (p < 0.05). The results of multivariate modeling showed that a low Barthel index score (at baseline and discharge), and intolerance to intensive rehabilitation were significant predictors of a requirement for home modification (p < 0.05). Conclusion: A low level of physical functioning and intolerance to intensive rehabilitation are significant predictors for the necessity of home modifications in stroke victims.